NILAI INDEKS TROMBOSIT SEBAGAI KONTROL KUALITAS KOMPONEN KONSENTRAT TROMBOSIT - Dewi Astuti (Meditory : The Journal of Medical Laboratory, 2020)
Platelet component therapy is given to patients who have thrombocytopenia and platelet dysfunction, therefore an assessment of the quality of platelet components is necessary. The platelet component evaluation in UTDD PMI DKI Jakarta was carried out on the parameters of blood type test, volume, platelet count, pH and macroscopic examination of platelets (swirling) once on days 1, 2 or 3. This study aims to determine the value of the platelet index during the shelf life of the platelet concentrate component as a quality control. The research method uses a cross sectional experimental approach. Platelet index analysis was performed using Sysmex SN 350 hematology analyzer on five platelet component samples. The quality of platelet components is assessed based on the presence or absence of the difference between the platelet index values during the shelf life. Statistical results show that there are significant differences in the values of MPV, PDW and PCT from the shelf life of the 2nd day until the 5th day, but the examination results are still within normal limits. Platelet index results show an increasing trend. This indicates an increase in platelet volume and variations in platelet form. The conclusion of this study, the platelet component has good quality until the 5th day, and the platelet index value can be used as a platelet quality control parameter.